Analyzing the Cultivating Impact of Political Awareness on the Political Participation and Efficacy of Pakistani Youth - Maqsood, Madiha; Gillani, Syeda Fatima; Bokhari, Sehreen Far (Annals of Human and Social Sciences, 2024)
The study investigates the cultivation effect of media on political efficacy and political participation of Pakistani youth. In democracies like Pakistan, Politics being the instrument of elites provides public an opportunity to take part in the process of government formation. Meanwhile, by using various forms of media for political awareness, Political communication holds the essential position to indulge the public. In developing countries where political instability is much evident, the influx of information on media adds to the political chaos creating distress in audience minds. A sample of 600 Pakistani youngsters (n=300) is selected through convenient sampling and then surveyed through a questionnaire developed on 5 points Likert scale. The results indicated a strong effect of political awareness provided by Pakistani media on the political participation and efficacy of youth.